Bone marrow mesenchymal stem cells transport connexin43 via tunneling nanotubes to alleviate isopreterenol-induced myocardial hypertrophy - Jianghui Zhang; Hongfeng Jiang; Sa Liu; Zhong Xian; Limin Zhao; Yue Li; Wenxiu Lu; Changrong Shao; Sanbao Chai (Stem Cell Research & Therapy)
Abstract Background Paracrine signaling plays an important role in stem cell therapy. However, it alone cannot fully explain the therapeutic mechanisms of stem cell therapy in treating heart diseases. Recently, tunneling nanotubes (TNTs)—a novel type of long-distance intercellular connectional structure—have been identified between mesenchymal stem cells (MSCs) and cardiomyocytes (CMs). TNTs mediate the transmission of multiple signaling molecules, enabling cells to exert different biological functions. In the present study, we investigated the role of TNTs in MSC-based therapy for myocardial hypertrophy. Methods MSCs And CMs were co Cultured for 24 h with or without isopreterenol (ISO) to induce myocardial hypertrophy. Confocal microscopy was used to quantify and analyze the number, morphology, composition, and cell source of TNTs between MSCs and CMs. the effects of ISO on CMs were assessed by comparing cell area (measured by confocal microscopy) and expression levels of hypertrophy Related genes (using qRT PCR) under co Culture and trans Well culture conditions. Flow cytometry was employed to assess the transfer of connexin43 (Cx43) from MSCs to CMs; lentivirus Mediated Cx43 overexpression and Cx43 siRNA were used to investigate the effects of Cx43 on ISO Induced myocardial hypertrophy. Results ISO stimulation significantly increased the number, length, and thickness of TNTs between MSCs and CMs (Number: P < 0.05; length and thickness: P < 0.01). ISO also increased the proportion of TNTs containing microtubules and those derived from MSCs (P < 0.05). Co-culture conditions were more effective than trans-well culture in alleviating ISO-induced myocardial hypertrophy (P < 0.05). Furthermore, Cx43 was observed in TNTs, and ISO enhanced the transfer of Cx43-mCherry from MSCs to co-cultured CMs (P < 0.05). Overexpression of Cx43 in CMs alleviated myocardial hypertrophy, whereas knocking down of Cx43 in MSCs reduced their ability to alleviate myocardial hypertrophy (P < 0.05). Conclusions Our results demonstrate that ISO promotes the formation of TNTs, particularly between MSCs and CMs, and induces changes in the morphology of TNTs (thickening and lengthening). Additionally, MSCs transmitted Cx43 to CMs via TNTs, which contributes to the alleviation of ISO-induced myocardial hypertrophy. These results suggest that TNTs represent an important mechanism in MSC-mediated therapy for myocardial hypertrophy.